The Legal Protection of Auction Winners Execution of Mortgage Guarantee Auction - Agustina, Erika Putri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Legal Protection for the winner of the Mortgage Execution Auction means that there is a legal certainty regarding an object for the winner of the Mortgage Auction Execution.In the auction process that has been carried out, there will be legal consequences, namely the transfer of the rights of the auction object from the seller to the auction winner. In practice, the transfer of rights to the auction object raises a problem, such as the auction winner being unable to control the object because it is controlled by a third party. The empirical juridical approach is that this research means that in analyzing the problem it is carried out by combining legal materials (which are secondary data) with primary data obtained in the field, namely regarding